Longitudinal validation and comparison of the Chinese version of the European Organization for Research and Treatment of Cancer Quality of Life‐Chemotherapy‐Induced Peripheral Neuropathy Questionnaire (EORTC QLQ‐CIPN20) and the Functional Assessment of Cancer‐Gynecologic Oncology Group‐Neurotoxicity subscale (FACT/GOG‐Ntx). Issue 1 (5th June 2018) - Cheng, Hui Lin; Molassiotis, Alex
Abstract: Aim: To validate and compare the Chinese version of the European Organization for Research and Treatment of Cancer Quality of Life‐Chemotherapy‐Induced Peripheral Neuropathy Questionnaire (EORTC QLQ‐CIPN20) and the Functional Assessment of Cancer‐Gynecologic Oncology Group‐Neurotoxicity subscale (FACT/GOG‐Ntx) for measuring chemotherapy‐induced peripheral neuropathy (CIPN) in cancer patients. Methods: Patients were assessed with the EORTC QLQ‐CIPN20, FACT/GOG‐Ntx, National Cancer Institute‐Common Terminology Criteria for Adverse Events (NCI‐CTCAE) and World Health Organization criterion of CIPN (WHO‐CIPN) from baseline up to 10 assessment points. Internal consistency reliability, convergent validity, discriminant validity and responsiveness of the EORTC QLQ‐CIPN20 and FACT/GOG‐Ntx were evaluated, respectively. Correlation and regression analysis were used to examine the relationships between these two scales. Results: Internal reliability coefficients for both scales were above 0.80 across all assessment points. Moderate correlations of the two scales were found with WHO‐CIPN ( r s  = 0.40–0.44; r s  = –0.42 to –0.46, all P  < 0.05) and NCI‐CTCAE ( r s  = 0.46–0.57; r s  = –0.44 to –0.55, all P  < 0.01) at most assessment points. Older patients reported significantly more CIPN symptoms than younger counterparts did ( P  < 0.05). The hypothesized factor structures of both scales were not confirmed ( χ 2/ df  = 3.70–7.01; χ 2/ df  = 2.14–10.43, all P  < 0.001). Both scales demonstrated responsiveness with small‐to‐moderate effect size ( r  = 0.09–0.46, r  = 0.11–0.35). The two scales were highly correlated and were predicted by all domains of each other at specific assessment points ( R 2  = 0.62–0.87; R 2  = 0.76–0.85; respectively, all P  < 0.001). Conclusion: The Chinese version of the EORTC QLQ‐CIPN20 and FACT/GOG‐Ntx demonstrated acceptable reliability, validity and responsiveness and was found comparable in measuring CIPN among Chinese cancer patients at specific assessment points.